2004
DOI: 10.1038/nmat1074
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembled liquid-crystalline gels designed from the bottom up

Abstract: Liquid crystals are often combined with polymers to influence the liquid crystals' orientation and mechanical properties, but at the expense of reorientation speed or uniformity of alignment. We introduce a new method to create self-assembled nematic liquid-crystal gels using an ABA triblock copolymer with a side-group liquid-crystalline midblock and liquid-crystal-phobic endblocks. In contrast to in situ polymerized networks, these physical gels are homogeneous systems with a solubilized polymer network givin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
98
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(102 citation statements)
references
References 32 publications
4
98
0
Order By: Relevance
“…In general, a gel is considered as a semi-rigid network in which a liquid is held. [26] However, the gel-like state induced because of ultralarge GO sheets prepared in our study exhibits fundamental characteristics that ordinary gels do not have. These characteristics include exceptional uniformity of the network structure (large domain LC), and the anisotropy arising from having LC in the network, which are the common features of liquid crystalline gel structures (solvent content > 99%).…”
Section: Birefringence Rheological Behavior and Spinnability Of Go Dmentioning
confidence: 60%
See 1 more Smart Citation
“…In general, a gel is considered as a semi-rigid network in which a liquid is held. [26] However, the gel-like state induced because of ultralarge GO sheets prepared in our study exhibits fundamental characteristics that ordinary gels do not have. These characteristics include exceptional uniformity of the network structure (large domain LC), and the anisotropy arising from having LC in the network, which are the common features of liquid crystalline gel structures (solvent content > 99%).…”
Section: Birefringence Rheological Behavior and Spinnability Of Go Dmentioning
confidence: 60%
“…These characteristics include exceptional uniformity of the network structure (large domain LC), and the anisotropy arising from having LC in the network, which are the common features of liquid crystalline gel structures (solvent content > 99%). [15,26] These unique features enable our as-prepared dispersions to be aligned by shear, as demonstrated by rheological studies, and ensure the preservation of the order even at low concentrations as they form a gel-like LC fiber as a result of wet-spinning.…”
Section: Birefringence Rheological Behavior and Spinnability Of Go Dmentioning
confidence: 90%
“…More recently, self-assembly of block copolymers has been used as an approach to create model liquid crystal networks [10 -12]. We have utilized self-assembly of a triblock copolymer that has a narrow molar mass distribution and a very long midblock to produce well-defined nematic gels [10,11]. This gel facilitates comparison to present theories which assume the material is lightly cross-linked and single phase.…”
mentioning
confidence: 99%
“…Mesogens with acrylate or methacrylate moieties, which are readily polymerised, may be varied to adapt the material properties. ABA triblock copolymers allow the construction of alternative structures, such as dilute gels [54]. Options for components and synthetic routes are discussed by Ohm [51], and other useful reviews may be found in Jiang et al [55], Chambers et al [56], and White et al [37].…”
Section: Skeletal Muscle-active Contractionmentioning
confidence: 99%